PENGUKURAN TINGKAT EFEKTIFITAS SISTEM INFORMASI PERPUSTAKAAN MENGGUNAKAN TEORI DELONE & MCLEAN - Rahmad Riza Bahrudin; M. Najibulloh Muzaki; Anita Sari Wardani (Universitas Methodist Indonesia, 2023)
The Reading Group of Gelaran Jambu Daar El-fikr or often called Gelaran Jambu was initiated and pioneered in 2008. It's located in Jambu Village, Kayen Kidul District, Kediri Regency. As an alternative education for local residents besides school, it is also a creative community that wants to develop personal potential through book-based education. Gelaran Jambu has more than 3000 books with various titles and genres. Children's books to adult books are available. Since September 2021 Gelaran Jambu has been using Senayan Library Management System (Slims), a web-based open-source application to fulfill library needs. Slims can be accessed for free and modified according to library needs. After the system has been operated for some time, it is necessary to measure its effectiveness to see the extent to which the goals have been achieved. Measuring the effectiveness of information systems using the Delone & Mclean IS Success Model theory with the Structural Equation Modeling (SEM) method. It is using a quantitative approach with descriptive statistical research techniques. The tool used to analyze the data is SmartPLS. The sample data used was 47. The results found three acceptable hypotheses and six hypotheses that were not accepted. The accepted hypotheses are System Quality to usage and User Satisfaction. And Usage to net benefits. Hypotheses that are not accepted: Information Quality to Usage and User Satisfaction, Service Quality to Usage and User Satisfaction, Usage to User Satisfaction, and User Satisfaction to Net Benefits.